Course of remission from and relapse to heavy drinking following outpatient treatment of alcohol use disorder. (1st June 2018) - Maisto, Stephen A.; Hallgren, Kevin A.; Roos, Corey R.; Witkiewitz, Katie
Highlights: Post-treatment change in alcohol use is a heterogeneous process. Individuals variably transition in and out of "relapse" and "remission" statuses. "Any heavy drinking" following treatment (tx) is not necessarily a sign of tx failure. Preventing heavy drinking and intervening quickly if it occurs seems most crucial. Evaluating "time to first heavy drinking episode" may not capture behavior change. Abstract: Background: We sought to understand alcohol behavior change as a process over time by identifying patterns of relapse and remission after outpatient treatment and evaluating how these patterns predict longer-term clinical outcomes. Method: We conducted latent profile analyses using data from the outpatient arm in Project MATCH. Relapse and remission episodes were defined by the number of consecutive 14-day periods that included any heavy drinking days and no heavy drinking days. Indicators of each profile were: initial 2-week post-treatment remission/relapse status, number of remission/relapse transitions in the first year after treatment, duration of remission episodes, and duration of relapse episodes. Results: We identified 6 profiles: 1) "remission, " 2) "transition to remission", 3) "few long transitions, " 4) "many short transitions, " 5) "transition to relapse, " and 6) "relapse." Profile 1 had the best long-term outcomes. Long-term outcomes were not uniform among individuals with at least some heavy drinking (profiles 2 through 6; ∼75% of the sample). Individuals who transitioned back to and sustained periods of remission (profiles 2–4) had better long-term outcomes than those who failed to transition out of relapse (profiles 5–6) following treatment. Conclusions: Post-treatment change in alcohol use is a process in which individuals variably transition in and out of "relapse" and "remission" statuses. "Any heavy drinking" following treatment is not necessarily a sign of treatment failure. A more nuanced look at the process of AUD change by considering whether individuals are able to transition to and sustain periods of remission seems warranted.